Didn't hear that coming: Effects of withholding phonetic cues to code-switching. Issue 5 (31st January 2020) - Shen, Alice; Gahl, Susanne; Johnson, Keith
Abstract: Code-switching has been found to incur a processing cost in auditory comprehension. However, listeners may have access to anticipatory phonetic cues to code-switches (Piccinini & Garellek, 2014; Fricke et al., 2016), thus mitigating switch cost. We investigated effects of withholding anticipatory phonetic cues on code-switched word recognition by splicing English-to-Mandarin code-switches into unilingual English sentences. In a concept monitoring experiment, Mandarin–English bilinguals took longer to recognize code-switches, suggesting a switch cost. In an eye tracking experiment, the average proportion of all participants' looks to pictures corresponding to sentence-medial code-switches decreased when cues were withheld. Acoustic analysis of stimuli revealed tone-specific pitch contours before English-to-Mandarin code-switches, consistent with previous work on tonal coarticulation. We conclude that withholding anticipatory phonetic cues can negatively affect code-switched recognition: therefore, bilingual listeners use phonetic cues in processing code-switches under normal conditions. We discuss the implications of tonal coarticulation for mechanisms underlying phonetic cues to code-switching.